2012
DOI: 10.1242/jeb.077370
|View full text |Cite
|
Sign up to set email alerts
|

Condition-dependent strategies of eggshell pigmentation: an experimental study of Japanese quail (Coturnix coturnix japonica)

Abstract: SUMMARYA relationship has been suggested between eggshell colour and female body condition based on the opposing antioxidant properties of the two main eggshell pigments: the antioxidant biliverdin (blue-green) and the pro-oxidant protoporphyrin (brown). We hypothesized that experimentally food-restricted females with low antioxidant capacity would deposit more protoporphyrin and less biliverdin in their eggshells, resulting in eggshells of reduced brightness but increased colour intensity. Two eggs were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 72 publications
(92 reference statements)
9
37
2
Order By: Relevance
“…This result also corresponds with our finding that eggs which contained lower concentrations of yolk antioxidants had more protoporphyrin pigment in the eggshell, although the oxidative status of females during the nestling feeding period showed no relationship with eggshell spotting pattern. Consistent with our results, Duval et al (2013) found that food-restricted Japanese Quail (Coturnix japonica) females deposited more protoporphyrin into their eggshells, suggesting that a higher pigment content in the eggshell may reflect poorer nutritional condition of the female.…”
Section: Eggshell Spotting and Female Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…This result also corresponds with our finding that eggs which contained lower concentrations of yolk antioxidants had more protoporphyrin pigment in the eggshell, although the oxidative status of females during the nestling feeding period showed no relationship with eggshell spotting pattern. Consistent with our results, Duval et al (2013) found that food-restricted Japanese Quail (Coturnix japonica) females deposited more protoporphyrin into their eggshells, suggesting that a higher pigment content in the eggshell may reflect poorer nutritional condition of the female.…”
Section: Eggshell Spotting and Female Traitssupporting
confidence: 90%
“…Several studies measured eggshell reflectance using a spectrophotometer and expressed it as brightness and red or brown chroma (Avilés et al 2007, Martínez-de la Puente et al 2007, Hanley and Doucet 2009, Maurer et al 2011b, Holveck et al 2012, Duval et al 2013, Krištofík et al 2013. Others determined pigment concentration of the eggshell by chemical analysis (Maurer et al 2011b, Cassey et al 2012, Duval et al 2013, Brulez et al 2014, or analyzed digitized pictures of eggshells to determine the percentage of spotted eggshell surface (Martínez-de la Puente et al 2007, Sanz and García-Navas 2009, Bulla et al 2012, Holveck et al 2012, Brulez et al 2014), or to determine hue, saturation, and brightness derived from HSB and RGB (Martínez-Padilla et al 2010, Cassey et al 2012, Holveck et al 2012), or to determine other spotting pattern variables, such as pattern contrast and marking size (Stoddard et al 2012). Finally, many studies used visual scoring of photographs, and spotting pattern was expressed as spot intensity, spot size, and spot distribution (Gosler et al 2005, Sanz and García-Navas 2009, López de Hierro and De Neve 2010, Bulla et al 2012, Holveck et al 2012, De Coster et al 2013, Hargitai et al 2013, Brulez et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the intensity of the blue-green colour of the eggs of the pied flycatcher (Ficedula hypoleuca), apart from being positively correlated with the biliverdin content of the eggshell, is also an indicator of the nutritional status of the laying females (Moreno et al, 2006). Duval et al (2013) reported that the eggshell of the eggs laid by female quails fed a diet with a restricted antioxidant capacity contained more protoporphyrin and less biliverdin. On the basis of these data, the researchers suggested that the brightness of the eggshell would decrease whilst the colour intensity of the eggshell would increase in eggs laid by female quails fed as such.…”
Section: Introductionmentioning
confidence: 99%
“…To attempt to find an answer to these questions, we used the brown-spotted cryptic eggs of the Japanese Quail (Coturnix coturnix japonica; hereafter ''quail''). Quail eggs represent a coloration typical of the egg crypsis of ground-nesting birds, with apparently distinct brown (protoporphyrin) cuticular pigment spots or blotches on the eggshells (Baird et al 1975, Soh et al 1993, Duval et al 2013. It should be stressed that in quails, egg speckling is the result of a superficial layer of brown pigmentation (a feature distinguishing other bird species studied in the context of the relationship between eggshell thickness and brown speckling; see above), which occurs immediately (~3 hr) before oviposition and is derived from pigment granules in the apical cells of the shell gland (Woodard and Mather 1964, Tamura et al 1965, Baird et al 1975.…”
Section: Introductionmentioning
confidence: 99%
“…Quail eggs have been used as a model in many previous experimental investigations to examine the maternal and environmental effects of variation in egg coloration in the context of the deposition of 2 basic eggshell pigments and to analyze the sources of variation in egg coloration patterns and pigment spot distributions. Female quails can promptly adapt the coloration of their eggs both to body condition (more heavily maculated eggs are laid by females with a poorer body condition; Duval et al 2013Duval et al , 2016 and to darkly colored substrates (Lovell et al 2013); such eggs are characterized by a greater hatchability and lower embryonic mortality (Taha 2011, Hassan et al 2013). Very recently, Duval et al (2016) reported some conflicting results on the role of speckling patterns in the accumulation of brown pigment in quail eggshells; they found that eggshell spot coverage was negatively correlated with the protoporphyrin concentration measured in entire eggshells, which suggests that protoporphyrin deposition does not increase the amount of visible brown spotting on the eggshell.…”
Section: Introductionmentioning
confidence: 99%